1982
DOI: 10.1002/j.1460-2075.1982.tb01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a new neurotrophic factor from mammalian brain.

Abstract: We report the purification from pig brain of a factor supporting the survival of, and fibre outgrowth from, cultured embryonic chick sensory neurons. The purified factor migrates as one single band, mol. wt. 12 300, on gel electrophoresis in the presence of sodium dodecylsulphate (SDS) and is a basic molecule (pI greater than or equal to 10.1). Approximately 1 microgram factor was isolated from 1.5 kg brain. The final degree of purification was estimated to be 1.4 X 10(6)‐fold, and the specific activity 0.4 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
735
2
13

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,626 publications
(757 citation statements)
references
References 20 publications
7
735
2
13
Order By: Relevance
“…Specifically, soluble Aβ oligomers are fundamental to promote neurotoxicity (Klein, 2001; Walsh & Selkoe, 2007) through different ways (Ferreira & Klein, 2011; Pearson‐Leary & McNay, 2012), including altered levels of neurotrophic factors (NTFs) (Calissano et al ., 2010; Budni et al ., 2015). Among these, brain‐derived neurotrophic factor (BDNF) (Barde et al ., 1982) is essential in sustaining physiological processes of the normal adult brain (Nagahara & Tuszynski, 2011), by tuning: (i) dendritic branching and spine morphology (Horch & Katz, 2002) and (ii) synaptic plasticity and long‐term potentiation (Figurov et al ., 1996) and therefore learning and memory. Interestingly, postmortem studies have shown that BDNF mRNA and protein decrease not only in end‐stage disease, but also in patients diagnosed with mild cognitive impairment (MCI) (Peng et al ., 2005), suggesting that a BDNF loss could be involved in the early synaptic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, soluble Aβ oligomers are fundamental to promote neurotoxicity (Klein, 2001; Walsh & Selkoe, 2007) through different ways (Ferreira & Klein, 2011; Pearson‐Leary & McNay, 2012), including altered levels of neurotrophic factors (NTFs) (Calissano et al ., 2010; Budni et al ., 2015). Among these, brain‐derived neurotrophic factor (BDNF) (Barde et al ., 1982) is essential in sustaining physiological processes of the normal adult brain (Nagahara & Tuszynski, 2011), by tuning: (i) dendritic branching and spine morphology (Horch & Katz, 2002) and (ii) synaptic plasticity and long‐term potentiation (Figurov et al ., 1996) and therefore learning and memory. Interestingly, postmortem studies have shown that BDNF mRNA and protein decrease not only in end‐stage disease, but also in patients diagnosed with mild cognitive impairment (MCI) (Peng et al ., 2005), suggesting that a BDNF loss could be involved in the early synaptic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…
Brain-derived neurotrophic factor (BDNF) is a small, basic protein purified from the mammalian brain that has been shown previously to support the survival of cultured spinal sensory neurons (Barde et al, 1982). In current studies, BDNF was tested for its ability to support the survival of cultured CNS cells isolated from the perinatal rat retina.
…”
mentioning
confidence: 99%
“…This brainderived neurotrophic factor (BDNF) has a molecular weight of 12,000 Da and an isoelectric point of about 10. It is known to support the survival of a variety of primary sensory neurons (connected to the CNS by their central axons) and to be inactive on both ciliary and sympathetic neurons (Barde et al, 1982;Davies et al, 1986;Lindsay et al, 1985).The current studies were conducted to determine if there is a population of CNS neurons that responds to BDNF in culture. The retina was chosen for these studies since we have previously shown that an extract prepared from pig brain stimulates neurite outgrowth from fetal rat retinal explants in culture (Turner et al, 1983).…”
mentioning
confidence: 99%
“…De nombreuses observations faites lors du déve-loppement de la moelle épinière, de la rétine ou du cervelet, suggéraient depuis longtemps l'existence de mécanismes équivalents dans le SNC. La découverte de molécules structurellement semblables au NGF, en particulier du BDNF qui est la neurotrophine de loin la plus abondante dans le SNC [5], a contribué à renforcer l'hypothèse selon laquelle les mécanis-mes contrôlant la survie des neurones dans le SNC pourraient être similaires à ceux opérant dans le SNP. Cependant, un nombre croissant d'observations ont montré de plus en plus clairement que même en l'absence complète de BDNF ou d'autres facteurs de croissance, le SNC se développe sans perte massive de neurones [6].…”
Section: Rôle Et Mode D'action Des Neurotrophinesunclassified